مساهمة المجلات المتخصصة في كتابة تاريخ الجزائر "مجلة أول نوفمبر 1972م-2015م أنموذجا" - بن باحان صابرين; د/ سعودي أحمد (جامعة عمار ثليجي الاغواط, 2023)
الملخص إن الصحف والمجلات والجرائد في العموم تنزل الستار عن الأحداث التاريخية الهامة، لتمكن القارئ لها من معرفة آراء ومواقف المثقفين والمؤرخين من مختلف الوقائع المختلفة في شتئ المجالات. مجلة أول نوفمبر تتمثل أهميتها بتقديم صور ووثائق عن ثورة التحرير، خشية من الاتلاف والاندثار والسعي لتخليد ذكريات الأحداث التاريخية التي مرت بها الثورة، فمن خلالها قام مجاهدي الثورة التحريرية وكتاب ومؤرخي الجزائر بنشر مقالات حول تاريخ الجزائر في الفترة المعاصرة. واختم عملي هذا بمقولة الرئيس الراحل الشاذلي بن جديد:" التاريخ هو ذاك رة الأمة وشعبيتجاهل تاريخه ولا يستلهم أمجاده هو شعب يفقد شخصيته وطموحاته وأصالته ويصبح عرضة للإسيتلاب الفكري وإلى التبعية التقليدية" . الكلمات المفتاحية: مجلة أول نوفمبر، تاريخ الجزائر، مجاهدي الثورة التحريرية. The summary: Newspapers, magazines, and newspapers in general reveal the important historical events, to enable the reader to know the opinions and positions of intellectuals and historians regarding the various facts in various fields. The November first magazine in important in presenting pictures and documents about the liberation revolution, for fear of Destroying and disappearing, and striving to perpetuate the memories of the historical events that the revolution went through, through which the fighters of the liberation revolution and the writers and historians of Algeria published articles on the history of Algeria in the contemporary period. I conclude this work with the saying of the late president Chadli Ben jedid:" History is the memory of the nation A people that ignores its history and is not inspired by its glories is a people that loses its personality, aspirations, and originality and becomes vulnerable to intellectual alienation and to traditional dependence". Keywords:1 November Magazine, History of Algeria, Mujahideen of the Liberation Revolution.